Controversies Around COVID-19 Vaccines and Antidepressants: Scope and Perspective in Malaysia - Chong Guan, Ng; Weng Hou, Siew; Abousheishaa, Aya Ahmed; Sue Yin, Low; bin Sulaiman, Abdul Rasyid; Chee Khin, Kok (Current Drug Research Reviews, 2023)
Background: Individuals with severe mental illness are prone to severe COVID-19 infection with increased morbidity and mortality. Psychiatric patients are often concerned about the potential interactions between the newly approved COVID-19 vaccines in Malaysia and psychotropic drugs like antidepressants. To date, such data are unavailable. Objectives: This review aims to clear the polemics of COVID-19 vaccine-antidepressants interaction in these 3 aspects: (1) cytokines and cytochrome P450 pathway, (2) blood-brain barrier (BBB) involvement and (3) and its interaction with polyethylene glycol (PEG), the potential allergenic culprit following COVID-19 vaccination. Methods: A scoping approach was employed to search for peer-reviewed journal articles across four healthcare and scientific databases (PubMed, MEDLINE, PsycINFO and Cumulative Index to Nursing and Allied Health Literature (CINAHL)). Results: Antidepressants metabolism often involves the CYP450 enzymes. Vaccine-antidepressants interactions are probable, likely to be triggered by interactions of CYP450 enzymes and inflammatory cytokines, resulting in diminished drug metabolism and chemical detoxification. Aside, PEG, the excipient in mRNA-based COVID-19 vaccines and antidepressants, has been reported as an anaphylaxis causative allergen. However, whether it leads to synergistic, potentiation or antagonistic effects when used in combination remains to be elucidated. ; Conclusion: Psychotropic medications, including antidepressants, showed potentially relevant safety risks for COVID-19 patients. These vulnerable patient group must be prioritized for early access to safe and efficacious COVID-19 vaccines, as vaccination remains the most important public health intervention to tackle the ongoing COVID-19 pandemic.
Keywords: cytochrome P450